Colorectal Neoplasm with Predominant Neuroendocrine Immunophenotype: Where does Adenocarcinoma End? - Cibulskaitė, Gabrielė; Stulpinas, Rokas; Poškus, Eligijus; Tulytė, Skaistė; Mickys, Ugnius (Lietuvos chirurgija, 2022)
MiNEN (mixed neuroendocrine-non-neuroendocrine neoplasm) is described in the 5th edition WHO classification of tumors of the digestive system as a mixed neoplasm, composed of neuroendocrine and non-neuroendocrine parts, each accounting for at least 30% of the tumor. Recently this formal criterion has been criticized based on the theory that both of these components could have a monoclonal origin and non-neuroendocrine cells develop neuroendocrinicity in the later evolutionary steps of adenocarcinoma. For this reason, the identification of pure adenocarcinoma component, that was overgrown by a more aggressive clone with neuroendocrine features, in a pathological specimen can be difficult and, in some cases, even impossible. So, it is likely that at least some of large cell neuroendocrine carcinomas follow the same pathway, a theory that is further supported by adenocarcinoma-like molecular alterations in these tumors. Precise diagnosis (which means identifying and naming each tumor component regardless of its size) is essential for a personalized treatment strategy. We present an illustrative case of a rectal neoplasm that could be classified as a poorly differentiated neuroendocrine carcinoma, but exhibits morphological heterogeneity, mucin production and has a typical KRAS mutation pointing to adenocarcinomatous origin, which makes MiNEN a more accurate diagnosis. The article discusses the key points in classification, pathogenesis, and diagnostic approach to help effectively manage such neoplasms.
Keywords: mixed neuroendocrine non-neuroendocrine neoplasm; MiNEN; mixed adeno-neuroendocrine carcinoma MANEC; large cell neuroendocrine carcinoma; colorectal neoplasm